(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The fast expansion and new advancement in the field ofscience and technology have steered the world into a new age. The developmentshave both pros and cons. On the one hand, technological developments haveaffected almost every aspect of human life, at the other; it has itsdevastating effects. Thus mankind faces double challenges from modern machinesand from saving the nature, the mother earth. At this paradoxical juncture, therole of media, so to say, becomes very important and worthwhile. In this modernknowledge-society, media plays the role of facilitator of development,disseminator of information, and being an agent of change. Regarding the issueof environment awareness, media play a vital role in spreading the message andsetting the agenda for the people. Besides bringing it to debates anddiscussions, the media propose alternatives to the people and policy-makers.The awareness also creates a genuine interest to probe into the exact matter.Thus, environment awareness is one of the important issues even in the field ofmedia. The awareness on environment has shown multiplicity of results in theform different issues of livelihood rights, of displacement and rehabilitation,of sustainability, of pollution led damages and its control etc. Thus, theall-pervading media has really raised the awareness on environment amongpeople.